Timber construction manual (New Jersey : John Wiley & Son, Inc., 2012)
"The Timber Construction Manual has become the definitive design and construction industry source for building with structural glued laminated timber. Revised to cover the 2011 National Design Specification for Wood from the National Forest Products Association, IBC 2009 ASCE 7-10, and AITC 117-2004, this new edition contains the latest design procedures for glulam construction and an expanded collection of real-world design examples supported with detailed schematic drawings. Information and recommendations are based on the most reliable technical data available and reflect commercial purposes found to be the most practical"-- Provided by publisher
Timber Construction -- Wood Properties -- Timber Design -- Timber Beams -- Timber Columns and Tension Members -- Timber Beam-Columns and Tension Beams -- Tapered Beams -- Curved Glulam Beams -- Glulam Arches -- Heavy Timber Decking -- Connections in Timber Structures -- Member Capacity at Connections -- Dowel-Type Fasteners -- Shear Plates and Split Rings -- Moment Splices -- Load and Resistance Factor Design -- Timber Bridges -- LRFD Bridge Design -- ASD Bridge Design -- Fire Safety.
Includes index.
Keywords: BUILDING, WOODEN -- HANDBOOKS, MANUALS, ETC